Pengaruh Latihan Playometrik Terhadap Peningkatan Power Otot Tungkai Pada Mahasiswa PGSD Atlet Bolavoli Putri SSC - Jusak Syaranamual (Elementary Teacher Education Program, Majalengka University, 2023)
The problem in this study is the low level of the explosive power of the athlete's limb muscles. This study aims to determine how much influence Plyometric training has on increasing leg muscle power in SSC Women's volleyball athletes. This research is an experimental study, in which the authors wanted to know the effect of Plyometric training on increasing leg muscle power in PGSD students, women's volleyball athletes, and SSC. The method used in this research is a field experiment method. The population used as the sample in this study was 10 PGSD students, so this research is called population research. The variables in this study consisted of the independent variable, namely plyometric training, and the dependent variable, namely the Power Test using the Jump MD measuring instrument. The instruments used in the training process consist of five forms of training. Based on the results of the pre-test and post-test which were processed using statistical formulas, the hypotheses in this study can be proven that there is an increase in leg muscle power in PGSD students, and SSC women's volleyball athletes through plyometric training.